THE EFFECT OF INTELLECTUAL CAPITAL EFFICIENCY ON FINANCIAL PERFORMANCE - Orleans Ritter; Henny Wirianata (International Journal of Application on Economics and Business, 2026)
In today's post-pandemic world, where economic recovery is key, smart handling of intangible assets is essential for boosting a company's overall worth. This research dives into how financial results tie into the effectiveness of intellectual capital within the non-cyclical consumer goods industry on the Indonesia Stock Exchange (IDX) from 2021 to 2024. It zooms in on the impact of three core elements—value added capital employed (VACA), value added human capital (VAHU), and structural capital value added (STVA)—on financial performance (ROA), all derived from the Value Added Intellectual Coefficient (VAICTM) framework. To gather data, the study relied on purposive sampling from audited financial statements of companies, creating a well-balanced panel dataset. Analysis was done using Microsoft Excel and Eviews version 12, with panel data regression as the main approach. After thorough checks, the Fixed Effect Model (FEM) turned out to be the most suitable for estimation. The results, backed by F-tests, t-tests, and checks for classical assumptions, reveal that VACA, VAHU, and STVA all positively and significantly boost ROA. These insights suggest that Indonesian consumer goods firms need to blend physical, human, and structural capital effectively to ramp up financial performance and achieve lasting growth in a tough market, underscoring why a full-on strategy for managing intellectual capital really matters.